IDENTIFYING PHRASEOLOGICAL UNITS IN ANECDOTES ABOUT KHOJA NASREDDIN - Xoliqberdieva Gulsanam Abdumutal qizi (Research Focus International Scientific Journal, 2025)
Khoja Nasreddin’s anecdotes, rich in humor and wisdom, often feature phraseological units (PUs) such as idioms, proverbs, and set expressions, which contribute significantly to the cultural and narrative depth of the stories. This study examines 50 anecdotes from Uzbek folklore, identifying and categorizing 150 PUs into idioms (60%), proverbs (25%), and set expressions (15%). The paper explores the narrative functions of these PUs, noting their role in advancing the plot and conveying moral lessons. Additionally, it addresses the challenges of translating these expressions into English, highlighting the difficulty of preserving their figurative meanings and cultural nuances. The study suggests translation strategies like dynamic equivalence and cultural adaptation to maintain the original meaning and humor. The findings emphasize the importance of PUs in Uzbek folklore and offer insights into the complexities of translating culturally specific linguistic features.